2022
DOI: 10.3389/fcimb.2022.1019071
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in recombinase polymerase amplification: Principle, advantages, disadvantages and applications

Abstract: After the outbreak of SARS-CoV-2, nucleic acid testing quickly entered people’s lives. In addition to the polymerase chain reaction (PCR) which was commonly used in nucleic acid testing, isothermal amplification methods were also important nucleic acid testing methods. Among several common isothermal amplification methods like displaced amplification, rolling circle amplification, and so on, recombinase polymerase amplification (RPA) was recently paid more attention to. It had the advantages like a simple oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 91 publications
(101 reference statements)
0
62
0
Order By: Relevance
“…These methods differ from each other in terms of amplification temperatures, sensitivities, reaction times, and other advantages and drawbacks (Gill and Ghaemi, 2008; Ivanov et al ., 2021). More recently, diagnostic assays based on RPA have become widely used for the molecular-based diagnosis of diseases (Tan et al ., 2022). The outbreak of SARS-CoV-2 has further promoted the application of RPA in nucleic acid detection (Bai et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods differ from each other in terms of amplification temperatures, sensitivities, reaction times, and other advantages and drawbacks (Gill and Ghaemi, 2008; Ivanov et al ., 2021). More recently, diagnostic assays based on RPA have become widely used for the molecular-based diagnosis of diseases (Tan et al ., 2022). The outbreak of SARS-CoV-2 has further promoted the application of RPA in nucleic acid detection (Bai et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak of SARS-CoV-2 has further promoted the application of RPA in nucleic acid detection (Bai et al ., 2022). Previous studies on RPA detection have shown several advantages of this technique, including its user-friendliness (in terms of simplicity of operations and low equipment requirements), high sensitivity, and great specificity (Tan et al ., 2022). Additionally, RPA best matches the requirement of ‘rapidity’.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has attracted great attention because it is insensitive to Taq polymerase inhibitors, and the DNA does not need to be isolated. Previous publications have reported the acceptable limit of detection of the assay [66,67]. Stringent optimization of reaction conditions is highly recommended, as inhibition may occur due to enzyme competition.…”
Section: Isothermal Amplification Of Nucleic Acid By Recombinant Poly...mentioning
confidence: 99%
“…The RPA technique requires amplification templates, primers and various components in addition to the two enzymes. [32] The process is probably that the recombinant enzyme protein forms a complex with the primers and then searches for the homologous sequence, and when it is found, it forms a d-loop structure to start the reaction. Micropropulsion reactor published by Tian et al based on Cas12a trans-cleavage activity and RPA studies.…”
Section: Strand Displacement Amplification (Sda)mentioning
confidence: 99%